A system design for cocoa beans transportation of premium products - T D M Sari; Y Arkeman; Muslich Muslich; D Taufik (IPTEK Journal of Proceedings Series, 2018)
Premium chocolate product such as praline, chocolate bars, confectionery, and chocolate drink need a premium quality of cocoa beans. Scarcity of sources and less quality in the existing cocoa beans supply chain affecting a sustainable production and increase operational cost. Improvement in cocoa supply chain which is consisting of farmers-farmers group- transporter/logistic provider- agro industry will provide cocoa beans availability and optimum operational cost of premium product-agro industry. Transportation sector which support supply chain has an important role for ensuring the distribution of cocoa beans delivery in time.  The source availability and transportation mode are the requirements that analyzed in Business Process Modelling (BPMN) to minimize transportation cost and maximize quantity of cocoa bean demand. The formulation of those will be optimized by Goal Programming. The results is deviation of transportation cost 2,083 rupiahs per kilogram when supply meets the agro industry demand and there is no deviation of transportation unit when using six unit of truck. It’s reveal that the availability of cocoa bean to meet agro industry demand will give cost efficiency.